THE EFFECT OF IMPLEMENTING DIGITALIZATION SYSTEMS ON THE VALUE OF BANKING COMPANIES: A META-ANALYST - Virzi Mutmainah; Lovvani Noralia; Listya Sugiyarti (PT. ZILLZELL MEDIA PRIMA, 2026)
This study was conducted with a meta-analysis to examine the influence of the digitalization system on the value of banking companies in Indonesia using secondary data from 19 SINTA and Scopus indexed journals for the 2020-2025 period. The sample consisted of 40-150 IDX banks with varying digitalization indicators (digital transaction ratio, digitization index, dummy implementation) and company value measurement using PBV, Tobin's Q, or market-to-book ratio. The analysis used a random effects model with Cohen's d to calculate the effect size. The results showed a moderate positive effect, namely Cohen's d = 0.42, 95% CI: 0.25-0.59, p<0.01 with a high heterogeneity of I²=82%, indicating inconsistency between studies. The influence is stronger in banks with a digitalization rate of >50%, the post-POJK period No. 12/POJK.03/2018 which is d=0.56, and banks in the BUKU 4 category which is d=0.62. No publication bias was found Egger's test p=0.12. This research strengthens the Growth Theory and recommends the adoption of a comprehensive digital strategy to increase the value of the company, with special attention to the efficiency of implementation and cyber risk management.